The Effectiveness of Writing Editorial Texts Learning with the Plural Partner Model A-21 Based on Vocation - Wulandari, Sri; Zulaeha, Ida; Wagiran, Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Editorial text writing skills involve the students’ abilities to collect references based on experience. Collaboration, communication, and critical and creative thinking activities are indispensable for learning in the 21st century. Plural Partner Model A-21 is used in learning activities to write editorial texts. This study aims to determine the effectiveness of learning to write editorial texts using the Plural Partner A-21 model based on the specialization of vocational students. The research design used was quasi-experimental with a population of XII grade students of SMK in the 2019/2020 academic year. Data collection techniques using test and non-test techniques. The test technique was carried out by measuring the skills of students in writing editorial texts, while the non-test technique was carried out by using questionnaire sheets, observation, and documentation. The data were analyzed using the T-test and analysis of variance (Anova). The results prove that the use of the Plural Partner A-21 model is effective in learning editorial text writing skills based on the specialization of vocational students. Research benefits provide theoretical and practical advantages. Theoretically, this study can enrich the theory of learning to write editorial texts using a combination of the Plural Partner model with 21st century learning skills. The importance of this research for educators to increase the sense of responsibility for the quality of education in an era of disruption.